Political Thought in Russia During the 21st Century, Targets and Features (Journal of the College of Education for Women, 2018)
The features of strategic thought transformation in Russia based on attempt confirm the Russian influenced on Region of Eastern Europe through series of common defense treaties and mutual security between USSR and another states this treaties emphasis size on direct Russian supervision on these states in addition, Russia in trusted to formation communism regimes in its vital space, Russia inherited the status of former USSR in political and economic levels. Shortly we can see that Russia witnessed large Transformation in political strategic thought as a result of change in internal strategic environment and change of nature understanding which influenced on Russia. This matter without doubt effaetion features of political and strategic thought in Russia at 21th century.Keywords: Political, Russia, Century.